SPECIALTY OF THE DESCRIPTION OF OLD BOOKS: BIBLIOGRA-PHICAL OR MUSEUM UNIT? - RANKELIENĖ, SONDRA (Knygotyra, 2011)
Vilniaus universiteto bibliotekaUniversiteto g. 3, LT-01122 Vilnius, LietuvaEl. paštas: Sondra.Rankeliene@mb.vu.lt